Shear Bond Strength of Bulk-Fill Composites to Resin-Modified Glass Ionomer Evaluated by Different Adhesion Protocols - Bin-Shuwaish MS (Dove Medical Press, 2020)
Mohammed S Bin-Shuwaish Department of Restorative Dental Sciences, College of Dentistry, King Saud University, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Mohammed S Bin-ShuwaishDepartment of Restorative Dental Sciences, College of Dentistry, King Saud University, Kingdom of Saudi ArabiaTel +966-11-467-7420Email malshowaish@ksu.edu.saObjective: The aim of this study was to investigate the shear bond strengths (SBS) of different nano-resin-based composites (RBCs) to resin-modified glass-ionomer cement (RMGIC) after the application of different adhesion protocols.Material and Methods: Three RBCs (Filtek One Bulk Fill [FOBF], Tetric N-Ceram Bulk Fill [TNCBF], and Filtek Z350 XT [Z350XT]) were used as layering materials over GC Fuji II LC RMGIC. Three adhesive systems — Total-etch (OptiBond Solo Plus [OB]), self-etch (CLEAR FIL SE Bond 2 [CFSE]), and a universal bond (Single Bond Universal [SBU]) — were used. In total, 160 RMGIC blocks were prepared. Ten samples (n = 10) were layered with the same material to form a reference-cohesive control group. The remaining samples were distributed among the following groups: No treatment [NT]; Total-etch [OB]; Self-etch [CFSE]; Universal bond in the “total-etch” mode [SBU-TE]; and Universal bond in the “self-etch” mode [SBU-SE]. Samples were stored, and aged by thermocycling (5000 cycles at 5 °C / 55 °C, 30 s) and then prepared for SBS testing. Fracture modes were examined by stereomicroscopy. Data were collected and analyzed statistically at a significance level of P< 0.05.Results: The highest mean SBS (14.30± 1.08 MPa) was reported in the OB group with the TNCBF material, while the lowest was in the NT group (5.05± 0.69 MPa) with FOBF. Samples in the NT group showed SBS statistically significantly lower than those of samples in all other groups (P< 0.0001). Bulk-fill materials had significantly higher SBS than Z350XT in OB, CFSE, and SBU-SE (P< 0.0001). SBU-TE produced SBS statistically significantly lower than those of other groups for FOBF (P< 0.0001), and lower than that of OB for TNCBF (P=0.027).Conclusion: OB, CFSE, and SBU-SE are reliable adhesion protocols for bonding bulk-fill RBCs to RMGIC when the “sandwich technique” is used for restorations. However, SBU-TE may not be effective in such procedures.Keywords: composite resins, bulk-fill, resin-reinforced glass ionomer, universal bond adhesive, bond strength